Obstetric Fistula Orientation Program in Nepal - Shakya, Tara (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To find out the hidden cases by strengthening/upgrading the knowledge of the participants and also to refer the identified cases not only to the phect -NEPAL's fistula surgery center (Kathmandu Model Hospital/Kirtipur hospital) but also to the nearest fistula centers of the country. Methods: In 2018, phect-NEPAL has conducted orientation program in seven districts. During the orientations, pretest/posttest was done with health service providers, female community health volunteers, NGOs /teachers and school students to see their knowledge on obstetric fistula. Public Health Concern Trust (phect-NEPAL) is working in this area not only in curative part but also in preventive/awareness part since 2014. Till now, phect-NEAPAL has conducted orientations in more than 17 districts (one Municipality and one village Municipality in each district). Results: Among the 370 health service providers who got orientation in 2018, a total of 90% of health service providers know what is obstetric fistula, 55% know about Pelvic organs involved in obstetric Fistula, 47 % HSP knows about the causes of obstetric fistula, 22% know about symptoms of obstetric fistula, only 37% know about diagnostic criteria for identifying obstetric fistula and 49% have confusing knowledge with other gynae problems like uterine prolapse. Among 660 FCHVs, almost 80 % of female community health volunteers did not heard about obstetric fistula. Those FCHVs who said they heard about obstetric fistula, more than 80% have confused knowledge of prolapse uterus /piles, leaking urine while coughing/sneezing, etc. Almost 90% of teachers and 60% of NGOs do not know about obstetric fistula. Conclusion: Awareness on obstetric fistula is a Key Component for successful implementation of Obstetric Fistula Program in Nepal.